Affects for stress reaction and hemodynamics by multimodal opioid free anesthesia on patients with video-assisted thoracoscopic surgery - WU Meichao; YANG Fangfang; CAI Ning; MA Xingjun (Zhongguo linchuang yanjiu)
Objective To compare the hemodynamics and stress reaction of opioid free anesthesia (OFA) and opioid anesthesia (OA) in patients undergoing video-assisted thoracoscopic surgery. Methods A total of 110 patients who underwent thoracoscopic bullectomy or lobectomy under general anesthesia at Fuyang People’s Hospital from January to October 2023 were randomly divided into OA group (n=55) and OFA group (n=55). Patients in OA group received OA combined with thoracic paravertebral nerve block during surgery, while the patients in OFA group used esketamine instead of opioids. Hemodynamic indicators [mean arterial pressure (MAP) and heart rate (HR)] and stress response indicators [blood glucose (Glu), cortisol (Cor), 8-isoprostaglandin F2α (8-iso)] at different time points and the dosage of propofol used during surgery were observed. Postoperative recovery time, Visual Analogue Scale (VAS) score and adverse reactions (nausea, vomiting, skin itching and mental symptoms) within 48 h after surgery were recorded. Results At the beginning of the study, 110 patients were included, of which 4 patients were excluded (1 patient was converted to open chest surgery, 1 patient experienced allergic reactions during surgery, and 2 patients were lost to follow-up). Finally, 53 cases were included in each of OA group and OFA group. Compared with the OA group, MAP and HR were significantly higher during induction, intubation and skin incision, while MAP and HR were significantly lower during extubation in OFA group (P＜0.05). And the dosage of propofol used during surgery was lower in the OFA group than that in the OA group [(428.4±147.5)mg vs (499.5±171.1) mg, t=2.291, P=0.024]. Besides, the incidence of postoperative nausea and vomiting was lower in the OFA group (1.89% vs 15.09%, χ2=4.371, P=0.037). There was no statistically significant difference in the stress response indicators (Glu, Cor, 8-iso), postoperative recovery time, incidence of skin itching and mental symptoms, and VAS score between two groups (P＞0.05). Conclusion Multimodal OFA using esketamine combined with thoracic paravertebral nerve block can effectively control surgical stress response, reduce intraoperative propofol dosage, maintain the circulatory system steady during anesthesia.